Série plaquetaŕria: Valores de referência e correlações observadas entre os parâmetros plaquetários em uma população aparentemente saudável - Silveira, M. M.; Fonseca, Luiz Marcos da [UNESP]; Guaglianoni, D. [UNESP] (My University, 2004)
Mean platelet volume (MPV), platelet distribution width (PDW) and plateletcrit (PCT) platelet parameters can be important to improve the initial identification of platelet disorders. The purpose of this study is to establish reference values for the platelet count (PLT), MPV, PDW and PCT in a population of 1346 apparently healthy adults, from both sexes, as well as to evaluate the correlations among these platelet parameters and to build the necessary nomograms for the clinical interpretations of the platelet indices. The platelet parameters were analyzed in blood samples collected into dipotassium ethylenediaminetetra-acetic acid (K 2 EDTA) by an electrical aperture-impedance method. There were non-linear and an inverse correlations between MPV and PLT, and between PDW and PLT, throughout the reference range of platelet count: the change in MPV and PDW was most accentuated at the lower platelet counts. Because of this non-linear inverse correlation, MPV versus PLT and PDW versus PLT nomograms were built. These correlations among the platelet parameters on a normal population provide a better understanding of these indices and may contribute to establish the real clinical significance of these platelet parameters in many diseases.
Platelet series: Reference values and correlations observed among the platelet parameters in an apparently healthy population
Keywords: Mean platelet volume; Nomogram; Platelet; Platelet parameters; edetic acid; blood sampling; cellular parameters; female; human; human experiment; male; normal human; platelet distribution width; plateletcrit; reference value; thrombocyte; thrombocyte count; thrombocyte volume